Time-dynamic associations between symptom-related expectations, self-management experiences and somatic symptom severity in everyday life: an ecological momentary assessment study with university students - Bernd Löwe; Yvonne Nestoriuc; Anne Toussaint; Stefanie Hahn; Franz Pauls; Simon Kirchhof (BMJ Open)
Objective The present study investigated the associations between symptom-related expectations, self-management experiences and expectation framing on somatic symptom severity in university students in two conditions (positive or standard expectation framing). We hypothesised that symptom-related expectations are significantly associated with concurrent and subsequent levels of somatic symptom depending on expectation framing.Design A smartphone-based micro-longitudinal ecological momentary assessment study with randomisation to one of two expectation framing groups (positive vs negative) was carried out. Multilevel mixed-effects linear regression analyses were conducted for data analysis.Setting Data was collected in real-time from university students via smartphones, with three predetermined assessments per day over seven consecutive days.Participants A total of 104 students (63.5% male, 0% diverse) who were 18 years or older, possessing sufficient German language skills and had access to an Android-powered smartphone were included.Interventions Participants were randomised to one of two different expectation framing groups, either receiving questionnaires for the expected impairment due to somatic symptoms (negative framing) or for the expected freedom from impairment due to somatic symptoms (positive framing).Primary outcome measures Somatic symptom severity was assessed using an adapted version of the Patient Health Questionnaire, with 11-point instead of 3-point Likert-scales. Symptom-related expectations were assessed using 11-point Numerical Rating Scales and self-management experiences were assessed using binary variables.Results Concurrent analysis revealed a significant association between symptom-related expectations and symptom severity (β=0.934, p<0.001), but no significant associations between self-management experiences and symptom severity. Regarding expectation framing, participants in the negative group reported higher symptom severity levels than those in the positive group (β=−0.071, p<0.001). Results indicated a stronger association between symptom-related expectations and symptom severity in the negative framing group (β=−0.088, p<0.001). Time-lagged analysis showed higher levels of symptom-related expectations predicted higher subsequent symptom severity levels (β=0.502, p<0.001), whereas preceding symptom severity levels or self-management experiences did not predict subsequent symptom severity levels. Negative framing was associated with higher subsequent symptom severity levels (β=−0.158, p<0.001). The effect of symptom-related expectations on subsequent symptom severity levels was independent of expectation framing.Conclusions Our findings highlight the impact of expectations and expectation framing on somatic symptom severity among university students and expand the knowledge needed for the development of expectation management techniques.Trial registration number ISRCTN36251388.